191k views
0 votes
SHOW WORK: Evaluate f(-2) with f(x)=3x+1 *

User Temuraru
by
4.7k points

2 Answers

4 votes

Explanation:


{:}\longrightarrow
\sf f (x)=3x+1


{:}\longrightarrow
\sf f (-2)=3 (-2)+1


{:}\longrightarrow
\sf f (-2)=-6+1


{:}\longrightarrow
\sf f (-2)=-5

User Screamin
by
5.7k points
1 vote

Answer:

f(2) = 7

Explanation:

Solve for f(-2) in f(x) = 3x + 1

x = -2

Plug in -2 for x in the equation:

f(2) = 3(2) + 1

Remember to follow PEMDAS. First, solve the multiplication, then add:

3 * 2 = 6

6 + 1 = 7

f(2) = 7 is your answer.

~

User Murat Erdogan
by
5.4k points